Immiscible hydrocarbon fluids in the deep carbon cycle - Fang Huang (Nature Portfolio, 2017)
Carbon migration in the deep Earth is still not fully understood. Here, the authors show that immiscible isobutane formsin situfrom transformation of aqueous sodium acetate at 300 °C and 2.4–3.5 GPa, indicating that hydrocarbon fluids may play a major role in carbon transfer in the deep carbon cycle.